Degraded or Just Dusty? Examining Ecological Change in Arid Lands. (26th June 2019) - Silcock, Jennifer L; Fensham, Rod J
Abstract: The ecological history of rangelands is often presented as a tale of devastation, where fragile drylands are irreversibly degraded through inappropriate land use. However, there is confusion about how to recognize and measure degradation, especially in low-productivity environments characterized by extreme natural variability and where abrupt and comprehensive management upheavals preclude benchmarks. These issues have important consequences for rangeland management programs, which are typically founded on presumptions of substantial and ongoing degradation from former "natural" states. We explore complementary approaches to critically assess degradation: the historical record, long-term grazing exclosures, surveys for potentially rare and sensitive plant species, and assessment of water-remote areas in relation to rare plant occurrence. Employing these approaches in inland Australia, we show that prevailing paradigms have become entrenched despite being inconsistent with empirical evidence. Our methodology can be applied to drylands with abrupt changes in management and contentious ecological narratives.